Research in varying burner tilt angle to reduce rear pass temperature in coal-fired boiler - Saravanan a/l Baskaran (2023)
As we all know coal fired power plants are widely used in Malaysiato generate electricity because it is readily available and cheap. All the coal power plants concern on the efficiency of the power plant to ensure proper combustion of the coal being used and reduce pollutant emissions.